Impact Of The Active Involvement In The Management Of Chronic Disease Program On The Blood Pressure Of Hypertensive Patients In Oesapa Public Health Center, Kupang City - Ida Ayu Dona Sasmita Maris Dona Sasmita Maris (Universitas Nusa Cendana, 2026)
Abstract Background: Hypertension or high blood pressure is one of the chronic diseases with a high prevalence in Indonesia. Therefore, the BPJS (Social Security Organizing Agency) creates a program to treat chronic disease called Prolanis (Chronic Disease Management Program) to improve the quality of life for the elderly. Objective: To determine the impact of the active involvement in the management of chronic disease program on the blood pressure of hypertensive patients in Oesapa public health center, Kupang City. Method: Observational analytical research with a cross-sectional study design is conducted on Prolanis participants at Oesapa Public Health Center. Data is derived from participants’ medical records and a questionnaire about the obedience of patients to take the medicine and deep interviews toward 32 research samples that fit in inclusion and exclusion criteria. The sample is taken using a purposive sampling technique. Data analysis is conducted by using univariate analysis and bivariate analysis using the coefficient contingency test. Result: The result of the research shows that active involvement in following Prolanis program has no significant impact on the blood pressure of elderly hypertensive patients (p value = 0.087). Conclusion: In conclusion, there is no correlation between the active involvement in following the management of chronic disease program and the blood pressure of hypertensive patients in Oesapa Public Health Center, Kupang City. Keyword: Hypertension, Prolanis, BPJS, Public Health Center, Kupang City.